Percepção dos estudantes de uma escola pública do estado do Rio Grande do Norte sobre a Caatinga e a Mata Atlântica: investigando através de aulas de campo virtuais e presenciais - Cunha, Márcio Gley (2022)
The Brazilian Biomes are almost always seen without their proper contextualization, leaving the student limited to memorizing concepts and visualizing some images, without relating them to the environment around them. The goal was then to develop field classes, as a didactic modality, making it an investigative tool that would provide students with a direct contact with their object of study, allowing them to build their own knowledge about the Caatinga and the Atlantic Forest, the only Biomes in Rio Grande do Norte. Besides diagnosing the students' knowledge about these environments, it can be characterized through research and contact with the fauna and flora (face-to-face and virtual) and also promote Scientific Literacy (CA), enabling, at the end of the process, to establish connections between the object of study and their daily lives. Given this scenario, the present work was carried out with 16 students from a third grade class of the Desembargador Vicente Lemos State School, in Senador Elói de Souza/RN. Qualitative and quantitative research was used as necessary approaches to understand the perceptions and participant observation to obtain data from the students about Biomes of RN. The data were collected from the application of two didactic sequences (DS) that were conducted remotely by Google Meet application, with synchronous and asynchronous moments in the period from February to September 2021, which were recorded, transcribed, analyzed, categorized and interpreted. The sequences had an emphasis on field classes, face-to face and virtual, with the development of scripts for face-to-face field trips by students individually or in pairs, respecting the protocols established by the decrees of the Health Secretariat of RN. The students explored the surroundings of their homes, having as orientation a collectively produced script, besides searches in video sites, about the studied environments, in which they could feel inserted. At the end of the activities, an evaluation questionnaire was applied to assess what they had learned. During the process, the student protagonism was evidenced in the production of the scripts, with the teacher acting as a mediator, and the students being active players in the process, aiming to verify the students' perception during and after the journey about Caatinga and Atlantic Forest. During the execution, a page was created on Instagram and as a final product a Teaching Guide of a "virtual field class", all mediated by the use of ICTs (YouTube, Google Meet, Google Forms, Instagram, Padlet, Poll Everywhere®, Playposit and WhatsApp). We conclude that the students were enthusiastic about doing the field classes and the internalization of knowledge was present in the answers of the evaluative questionnaire, as well as during the whole process, evidenced by the chain of ideas brought to the discussion, in which the central problems brought new elements to the debate and the curiosity in searching for answers was always present throughout the process.